2005
DOI: 10.2166/ws.2005.0096
|View full text |Cite
|
Sign up to set email alerts
|

Predicting water pipe breaks using neural network

Abstract: The relationships between pipe breaks of service pipes and mains and several factors were examined. Historical pipe breaks, and water and soil temperatures were also modeled by an artificial neural network to predict pipe breaks for efficient management and maintenance of the pipe networks. It was observed that the breaks of pipes increased after the temperatures of water and soil crossed in spring and fall. The pipe breaks were closely related to water and soil temperature, especially mains were affected more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Schuster and McBean (2008) and O'Day (1982) derived failure probability models based on the time of previous failures, soil types, pipe diameters, environmental conditions and age. Ahn et al (2005) observed that most types of pipes (ductile iron, steel, and asbestos cement) did not have an increased number of failures during the colder winter months but that cast iron did show a significant increase in the number of failures during the winter months.…”
Section: Precedent Models For Watermain Failurementioning
confidence: 93%
See 1 more Smart Citation
“…Schuster and McBean (2008) and O'Day (1982) derived failure probability models based on the time of previous failures, soil types, pipe diameters, environmental conditions and age. Ahn et al (2005) observed that most types of pipes (ductile iron, steel, and asbestos cement) did not have an increased number of failures during the colder winter months but that cast iron did show a significant increase in the number of failures during the winter months.…”
Section: Precedent Models For Watermain Failurementioning
confidence: 93%
“…The models were trained with historical input data including temperature, rainfall, operating pressure, and number of breaks. Ahn et al (2005) used an ANN model for predicting water pipe breaks in service pipes and mains in Seoul (Korea); they observed good performance for a prediction model based on pipe characteristics and water and soil temperatures. Moselhi and Shehab-Eldeen (2000) employed an ANN in the analyses and classification of defects in sewer pipelines.…”
Section: Precedent Models For Watermain Failurementioning
confidence: 99%
“…Although, Ahn et al (2005) indicate that their model was able to predict the number of breaks, there is insufficient detailed information to assess if the data they present explained the influence of water or soil temperatures on main breaks. Again the analyses were conducted on data collected over a one year period.…”
Section: Review Of Past Studiesmentioning
confidence: 95%
“…The authors claimed that the model was successfully applied to a holdout sample, demonstrating that the ANN "learned" the breakage patterns rather than memorized them 2 . Ahn et al (2005) explored the use of ANN to relate breaks to water and soil temperatures.…”
Section: Review Of Past Studiesmentioning
confidence: 99%
“…Reliability of water distribution networks relates to two types of failure, mechanical failure of system components and hydraulic failure caused by changes in demand and pressure head (Tabesh 1998 age (Shamir & Howard 1979), age and diameter (Kettler & Goulter 1985;Giustolisi et al 2006), diameter (Kettler & Goulter 1983;Su et al 1987;Goulter & Kazemi 1988, 1989Mays 1989;Cullinane et al 1992;Goulter et al 1993;Tabesh & Abedini 2005), climatic conditions (Harada 1988;Sacluti 1999;Welter 2001;Ahn et al 2005 (Su et al 1987;Fujiwara & Tung 1991;Cullinane et al 1992;Khomsi et al 1996). All these formulae involve pipe failure rate but, as will be seen in this paper, they produce different results.…”
Section: Introductionmentioning
confidence: 99%